A continuous coupled hydrological and water resources management model. (January 2016) - Bellin, Alberto; Majone, Bruno; Cainelli, Oscar; Alberici, Daniele; Villa, Francesca
Abstract: Human exploitation of water resources is widespread and its impact on hydrological fluxes is expected to increase in the future. Water use interacts in a complex manner with the hydrological system causing severe alterations of the hydrological fluxes with multifaceted feedbacks. Implementing this coupling within hydrological models is essential when dealing with the impact of human activities on water resources at all relevant scales. We contribute to the effort in developing models coupling natural and human systems with a distributed continuous model, named GEOTRANSF. The model allows to quantify, within the same framework, alterations in the natural regime and constraints and limitations to water resources availability. After presenting GEOTRANSF, an example of application to a medium-size Alpine catchment with streamflow modified by hydropower and distributed uses is discussed, followed by the analysis of the effect of suitable water uses scenarios in the same catchment. Highlights: Novel modeling approach coupling hydrological and human systems. Small water uses are accounted for in an exact manner. Assessment of different scenarios of water resources exploitation within the catchment.